Microscopic profile control mechanism and potential application of the biopolymer-producing strain FY-07 for microbial enhanced oil recovery. (16th December 2016) - Bi, Y. Q.; Yu, L.; Huang, L. X.; Ma, T.; Xiu, J. L.; Yi, L. N.
ABSTRACT: To promote the application of strain FY-07 in oilfield development, experiments were performed on the mechanism of microscopic profile control using an etched glass micromodel. The physical simulation experiments were applied to evaluate the plugging ability and oil displacement performance. The results showed that the biopolymers were preferentially generated and existed in large pores that can improve the swept volume and oil recovery. The plugging rate of FY-07 for different permeability cores was 67–78%, which indicates FY-07 exhibited good plugging capacity. The EOR value of FY-07 was 10.54%, which demonstrated that FY-07 has great potential to enhance oil recovery.